2015
DOI: 10.1309/ajcpwsl3g8rxmcqr
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Treponemal Serum Tests Performed on Cerebrospinal Fluid for Diagnosis of Neurosyphilis

Abstract: Objectives We evaluated the use of treponemal serum tests in cerebrospinal fluid (CSF) to diagnose neurosyphilis since CSF–Venereal Disease Research Laboratory (VDRL) is specific but lacks sensitivity. Methods We tested CSF specimens using the following treponemal serum tests: INNO-LIA, Treponema pallidum particle agglutination (TP-PA), Trep-Sure, and Maxi-Syph. The reference standard to calculate sensitivity and specificity was having two or more reactive/positive tests on CSF. Results The reference stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…The primary finding of our study was a remarkable diversity of tests, which had different purposes (diagnostic confirmation, screening), varied techniques (clinical signs/symptoms, serological analysis, CSF assessment), and a heterogeneous evaluation methodology (including or not HIV-positive individuals, including or not asymptomatic patients, comparing or not with controls, etc.). Most of the articles studied CSF alterations, measuring cells, proteins, treponemal and nontreponemal antibodies [ 16 20 ], or applied new immunological/biomolecular techniques [ 21 25 ]. Three papers assessed the significance of blood parameters to distinguish between NS+ and NS- [ 26 28 ], and only one considered clinical signs or symptoms in the investigation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary finding of our study was a remarkable diversity of tests, which had different purposes (diagnostic confirmation, screening), varied techniques (clinical signs/symptoms, serological analysis, CSF assessment), and a heterogeneous evaluation methodology (including or not HIV-positive individuals, including or not asymptomatic patients, comparing or not with controls, etc.). Most of the articles studied CSF alterations, measuring cells, proteins, treponemal and nontreponemal antibodies [ 16 20 ], or applied new immunological/biomolecular techniques [ 21 25 ]. Three papers assessed the significance of blood parameters to distinguish between NS+ and NS- [ 26 28 ], and only one considered clinical signs or symptoms in the investigation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) [ 7 ] recommends performing a lumbar puncture and CSF analysis for VDRL and FTA-ABS to detect neurological involvement in people with ocular syphilis. This examination is mandatory in patients with syphilitic optic neuritis and in the case of abnormal CSF results, it is repeated serially every six months to assess treatment response [ 7 , 9 , 10 ]. MRI, in turn, has found application in the detection of gummatous involvement of the CNS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to CSF-FTA-ABS, CSF-TPPA does not require specialized equipment and determination of a titer is straightforward. In a few studies, CSF-TPPA has been shown to be highly sensitive (4,5), and the use of a cutoff value for CSF-TPHA, a test similar to CSF-TPPA, increases the specificity for neurosyphilis diagnosis (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivities of CSF treponemal tests are greater than 90% when neurosyphilis is defined as a reactive CSF-VDRL and are lower when the diagnosis of neurosyphilis is based on clinical findings (3). Limited data on the use of the CSF Treponema pallidum particle agglutination assay (CSF-TPPA) for neurosyphilis diagnosis suggest that, like CSF-FTA-ABS, it may be diagnostically sensitive (4,5). The Treponema pallidum hemagglutination assay (TPHA) is similar to TPPA, and two studies have suggested that a CSF-TPHA titer of Ն1:640 is specific for neurosyphilis diagnosis (6,7).…”
mentioning
confidence: 99%